Patient-Centered Care Through Nurse Practitioner–Led Integrated Behavioral Health: A Case Study. (May 2023) - Weston, Cindy; Wells-Beede, Elizabeth; Salazar, Alice; Poston, Doris; Brown, Sandra; Hare, Martha; Page, Robin
Integrated behavioral health can improve primary care and mental health outcomes. Access to behavioral health and primary care services in Texas is in crisis because of high uninsurance rates, regulatory restrictions, and lack of workforce. To address gaps in access to care, a partnership formed among a large local mental health authority in central Texas, a federally designated rural health clinic, and the Texas A&M University School of Nursing to create an interprofessional team-based health care delivery model led by nurse practitioners in rural and medically underserved areas of central Texas. Academic–practice partners identified 5 clinics for an integrated behavioral health care delivery model. From July 1, 2020, through December 31, 2021, a total of 3183 patient visits were completed. Patients were predominantly female (n = 1719, 54%) and Hispanic (n = 1750, 55%); 1050 (33%) were living at or below the federal poverty level; and 1400 (44%) were uninsured. The purpose of this case study was to describe the first year of implementation of the integrated health care delivery model, barriers to implementation, challenges to sustainability, and successes. We analyzed data from multiple sources, including meeting minutes and agendas, grant reports, direct observations of clinic flow, and interviews with clinic staff, and identified common qualitative themes (eg, challenges to integration, sustainability of integration, outcome successes). Results revealed implementation challenges with the electronic health record, service integration, low staffing levels during a global pandemic, and effective communication. We also examined 2 patient cases to illustrate the success of integrated behavioral health and highlighted lessons learned from the implementation process, including the need for a robust electronic health record and organizational flexibility.